2016
DOI: 10.1063/1.4959218
|View full text |Cite
|
Sign up to set email alerts
|

Bi-alkali antimonide photocathode growth: An X-ray diffraction study

Abstract: Bi-alkali antimonide photocathodes are the best known sources of electrons for high current and/or high bunch charge applications like Energy Recovery Linacs or Free Electron Lasers.Despite their high quantum efficiency in visible light and low intrinsic emittance, the surface roughness of these photocathodes prohibits their use as low emittance cathodes in high accelerating gradient superconducting and normal conducting radio frequency photoguns and limits the minimum possible intrinsic emittance near the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Although it is well known that the CsK 2 Sb cathode performance depends on the substrate material and surface conditions [13,[18][19][20][21], the underlying physics has not been extensively studied to date because of the lack of standardization of the cathode evaporation process. For example, the dependence of the cathode performance on the surface orientation of the CsK 2 Sb or the substrate crystal was studied but not significantly observed [22,23] because the cathode evaporation condition was not fully optimized in these studies. Indeed, the QE in these studies was relatively low (3%).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that the CsK 2 Sb cathode performance depends on the substrate material and surface conditions [13,[18][19][20][21], the underlying physics has not been extensively studied to date because of the lack of standardization of the cathode evaporation process. For example, the dependence of the cathode performance on the surface orientation of the CsK 2 Sb or the substrate crystal was studied but not significantly observed [22,23] because the cathode evaporation condition was not fully optimized in these studies. Indeed, the QE in these studies was relatively low (3%).…”
Section: Introductionmentioning
confidence: 99%
“…Models suggest that at the envisaged gradients for SRF photoinjectors (15)(16)(17)(18)(19)(20) the surface roughness of the photocathode must be reduced to values of R q ≤ 10 nm to maintain a roughness induced emittance contribution that is below the intrinsic emittance [9,10]. From recent works of Schubert et al and Ding et al it is apparent that the final roughness of alkali antimonide photocathodes depends strongly on the growth procedure and the crystallization processes involved [11,12]. It has been shown that the sequential growth process delivers very rough photocathodes due to the multiple phase transitions, while smoother photocathodes can be grown using new growth procedures such as triple evaporation of Cs-K-Sb using pure alkali metal sources and magnetron sputtering [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…From recent works of Schubert et al and Ding et al it is apparent that the final roughness of alkali antimonide photocathodes depends strongly on the growth procedure and the crystallization processes involved [11,12]. It has been shown that the sequential growth process delivers very rough photocathodes due to the multiple phase transitions, while smoother photocathodes can be grown using new growth procedures such as triple evaporation of Cs-K-Sb using pure alkali metal sources and magnetron sputtering [13][14][15][16]. In this work an adaptation of a codeposition procedure has been developed, taking into consideration the geometrical condition of our preparation system.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques allow the evaluation of material composition, crystal structure, electrical conductivity, surface morphology (roughness, lateral structure), layer thickness and the extent of interdiffusion, doping concentrations, and other relevant material properties. In some cases, additional insight can be obtained by making these measurements in operando -during the growth process 138,139 allowing for adjusting growth parameters to account for material incorporation into the film during growth. A materials-centric approach to photocathode development now requires the availability of some combination of such techniques.…”
Section: In Situ Surface Science Characterizationmentioning
confidence: 99%